Assessment of Groundnut Elite Lines under Drought Conditions and Selection of Tolerance Associated Traits - Achirou Bacharou Falke; Falalou Hamidou; Oumarou Halilou; Abdou Harou (Advances in Agriculture)
Investigation of groundnut genotypes response to drought stress could contribute to improving drought tolerance and productivity. The objective of this study was to investigate new improved groundnut varieties response to drought stress under controlled conditions to identify tolerant materials and drought tolerance related traits. Thus, three experiments were conducted during off-seasons: two experiments in lysimetric system in 2017 and 2018 and one experiment in pots in 2017, to assess twelve varieties in a randomized complete block design with 2 water regimes and 4 replications. The water regimes were a full irrigation (WW) and an intermittent drought imposed at flowering times (WS). The investigated morphophysiological traits like transpiration, specific leaf area, root dry matter, root length density, and yield components decreased under WS. Significant year effect and genotypic variation were observed on most of investigated traits. Genotypes ICGV 92206 and ICGV 06319 showed low transpiration and revealed high pod yielding and early maturing genotypes under both water regimes, while genotypes ICGV 92035, ICGV 92195, ICGV 02038, ICGV 07211, and ICGV 07210 were drought-sensitive for pods production but produced high haulm under both water regimes. ICGV 92206, ICGV 02005, ICGV 02125, and ICGV 06319 showed higher yielding than 55-437 and Fleur 11. In this study, low total transpiration to control water loss, chlorophyll content, and root length density revealed drought tolerance associated traits for pod production, while TTW, TE, RDW, and RV revealed drought tolerance associated traits for fodder production.